Secure Authorized Deduplication Based on Hybrid Cloud Approach - Suresh, J; Jhansi Rani, S (International Journal of Computer Sciences and Engineering, 2025)
Data de-duplication is a data compression technique which is used to eliminate the duplicates for the repeated data. It is been extensively used in the cloud storage to minimize the amount of storage size and save maximum bandwidth. The convergent technique is been suggested, to encrypt the data before outsourcing to protect the confidentiality for the sensitive data while using de-duplication. In order to provide better data security, a hybrid cloud is been proposed. A hybrid cloud is a combination of private cloud and public cloud bound together. Private cloud is a place where some critical activities can be performed like security, setting the privileges to the users, setting the token number etc. whereas the public cloud is a place where some noncritical activities are performed like outsourcing an encrypted file. This paper formally addresses authorization with data de-duplication; we present several new de-duplications supporting the authorized duplicate check in the hybrid cloud architecture. In this paper we attempt to address the authorized de-duplication check, combined with convergent encryption for providing the better security to the sensitive data using the hybrid cloud architecture.